PERSPEKTIF KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA STAF ADMINISTRASI PADA UNIVERSITAS ISLAM MAKASSAR - Muliati, Muliati; Ernawati, Ernawati (Jurnal Dakwah Tabligh, 2020)
Transformational leadership has a positive and significant effect on the performance of Administrative Staff. Human resources or employees must always be considered, maintained, and maintained, and developed by the organization. Therefore, the administrative staff is valuable assets owned by tertiary institutions in carrying out institutional duties based on the tri dharma of tertiary institutions. Descriptive research was conducted by interview and questionnaire distribution, while the Transformational Leadership variable with indicators of Idealized influence, Inspirational motivation, Intellectual Stimulation, and Individualized consideration or individualized attention, all had gone well. With these results, this study is in line with Bass (1985) in Yukl (2013, p.313) that transformational leadership is a condition where followers of a transformational leader feel trust, admiration, loyalty, and respect for the leader, and they are motivated to do more than they initially expected. This condition is reflected in academic life at Makassar Islamic University which has a woman leader.